Satisfaction and Constraints in Accessing Services of Soya Choupal: A Case of Madya Pradesh (Indian Journal of Extension Education, 2011)
The satisfaction and constraints of farmers in accessing the services of soya choupal was studied in the indore district of Madhya Pradesh. A sample of sixty soya choupal farmers was drawn through random sampling technique. The soya choupal provides a number of services, which the rural communities need, from input supply to marketing of the final produce. Among the services, market prices always before selling their soybean produce. A high level of overall satisfaction towards the use of soya choupal services was felt by 50.0 per cent of farmer. About 40.0 per cent were found in medium level of overall satisfaction. The soya choupal farmers ranked power breakdown as the most important constraint followed by internet connectivity and poor transport facilities.